Systemic treatment for primary malignant sarcomas arising in craniofacial bones - Bielack, Stefan S. (Frontiers in Oncology, 2022)
Introduction Craniofacial bones may be the site of origin of various sarcomas. We review the various malignancies affecting this region of the body and attempt to put systemic treatment approaches into perspective. Material and methods Non-systematic literature review Results Conventional types of osteosarcoma, Ewing sarcoma, and chondrosarcoma are the most frequent bone sarcomas occurring in craniofacial region, but variants may occur. The tumors’ biologies and the resulting treatment strategies vary distinctly. As a general rule, local control remains paramount regardless of histology. The efficacy of antineoplastic chemotherapy varies by type of malignancy. It is clearly indicated in Ewing sarcoma and related tumors, potentially of benefit in high-grade osteosarcoma, undifferentiated pleomorphic sarcoma, dedifferentiated and mesenchymal chondrosarcoma, and of no proven benefit in the others. Conclusions Various histologies demand various and distinct treatment approaches, with local control remaining paramount in all. The efficacy of systemic treatments varies by type of tumor. Prospective trials would help in all of these to better define systemic treatment strategies.